2016
DOI: 10.1007/s00259-016-3379-4
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured human Achilles tendon has elevated metabolic activity up to 1 year after repair

Abstract: These data demonstrate that the healing process as determined by metabolic activity and vascularization continues for 6 months after injury when large loads are typically allowed on the tendon. Indeed, metabolic activity remained elevated for more than 1 year after injury despite normalized vascularization. The robust negative correlation between tendon metabolism and patient-reported outcome suggests that a high metabolic activity 6 months after the injury may be related to a poor clinical healing outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 26 publications
4
52
1
Order By: Relevance
“…If the latter scenario is true, such a failure to regain normal pre-injury values would be supported by a previous study, which demonstrated that ruptured human Achilles tendons may have elevated metabolic activity up to one year post-injury. 39 Tendons with IM1/ACT5 were significantly more likely to exhibit GAG staining than IM6/ACT0 tendons, which may suggest a potential compositional downside to returning to sport early. When compared to data 3-weeks post-injury, GAG deposits were more prevalent in tissues 6-weeks post-injury, suggesting that there is a temporal response to GAG accumulation in Achilles tendons following rupture.…”
Section: Discussionmentioning
confidence: 95%
“…If the latter scenario is true, such a failure to regain normal pre-injury values would be supported by a previous study, which demonstrated that ruptured human Achilles tendons may have elevated metabolic activity up to one year post-injury. 39 Tendons with IM1/ACT5 were significantly more likely to exhibit GAG staining than IM6/ACT0 tendons, which may suggest a potential compositional downside to returning to sport early. When compared to data 3-weeks post-injury, GAG deposits were more prevalent in tissues 6-weeks post-injury, suggesting that there is a temporal response to GAG accumulation in Achilles tendons following rupture.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, Eliasson, et al . 12 reported an elevated metabolic activity, particularly glucose uptake, in ruptured Achilles tendons up to 1 year after surgical repair. Further, we previously described a tendon cell population in human and rat tendons, which upon glucose stimulation secretes insulin 13 .…”
Section: Introductionmentioning
confidence: 95%
“…In addition to muscle atrophy, tendon length has received attention in recent years as an explanation of the suboptimal function. The Achilles tendon tissue can undergo extensively elongation in the initial 12 weeks, and all the way up to 26 weeks after surgery, while the metabolic activity and stiffness of the tendon may take up to a year to normalize . Importantly, the tendon elongation appears to be related to the clinical outcome and muscle function, such that less elongation yielded a better outcome .…”
Section: Introductionmentioning
confidence: 99%